Inovasi Perkebunan Cabai Di Kelurahan Bonto Manai Kecamatan Bissappu Kabupaten Bantaeng - Indrayanti, Kiki Resky; Abdi, Abdi; Riskasari, Riskasari (Universitas Muhammadiyah Makassar, 2021)
The aim of this study was to determine the development of chili plantation production, as well as supporting factors and inhibiting factors for chili plantation in Bonto Manai Village, Bissappu Sub-district, Bantaeng Regency. This study used a qualitative descriptive approach. The number of informants was 5 people. Data collection techniques were interview, observation, library research and documentation. The results of this study showed that the innovation of chili plantations in Bonto Manai Village, Bissappu Sub-district had carried out the expansion of land in chili plantations and the management system used a multifator tool for making beds in chili plantations and had supporting factor from non-governmental organizations because it could help to manage plantations and the existence of multifator tool loans from the community to support the development of chili plantations in the Bonto Manai Village, Bissappu Sub-District. The inhibiting factor of the chili plantation was the limited costs in purchasing seeds of superior quality. Limitations of the equipment in the cultivation process to the harvest process